(untitled) (The Research of Medical Science Review, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a major global health issue, contributing significantly to morbidity and mortality. It is frequently associated with comorbidities such as Deep Vein Thrombosis (DVT), a serious venous thromboembolic condition. Understanding the prevalence and risk factors of DVT in COPD patients is essential for improving clinical outcomes. Objective: To determine the frequency of DVT among COPD patients at Punjab Institute of Cardiology, Lahore, and to identify associated demographic and clinical risk factors. Methods: A descriptive cross-sectional study was conducted from August 2023 to January 2024, involving 240 patients aged 30–70 years with a confirmed COPD diagnosis. Doppler ultrasonography was performed to detect DVT. Data on age, gender, smoking history, hypertension, diabetes, obesity, dyslipidemia, disease duration, socioeconomic status, and residential status were collected and analyzed using SPSS version 23.0. Associations were assessed using the chi-square test, with a p-value fi 0.05 considered significant. Results: The prevalence of DVT was 11.3% (27/240 patients). Significant associations were found with smoking history (p < 0.001), hypertension (p < 0.001), obesity (p = 0.027), and disease duration exceeding one year (p < 0.001). No significant associations were observed with gender, age, residence, socioeconomic status, diabetes, or dyslipidemia. Conclusion: The study highlights a notable prevalence of DVT among COPD patients, with smoking, hypertension, obesity, and prolonged disease duration as key risk factors. Routine DVT screening and prophylactic measures should be integrated into COPD management to reduce complications and improve patient outcomes.